2010
DOI: 10.1007/s10552-010-9528-3
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and childhood cancer incidence in the United States

Abstract: This study examined socioeconomic differentials in cancer incidence rates during 2000-2005 among children aged 0-19 in the United States. The data on childhood cancers, which were classified by the International Classification of Childhood Cancer, Third Edition (ICCC-3), were obtained from the Surveillance, Epidemiology, and End Results program. The socioeconomic status of residential area at diagnosis was estimated by county-level poverty rate in Census 2000, i.e., percentage of persons in the county living b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 19 publications
2
36
1
Order By: Relevance
“…In contrast, a pooled population-based analysis of five US states, which included California births from 1988–1997, did not find an association with maternal education [37]. A nationwide US study also suggested a lower risk of GCTs in higher-poverty areas, but poverty metrics were on the county-level, making results difficult to compare to our individual or census-tract level measures [38]. The small number of studies, and the varying measures of socioeconomic status used, suggest a need for more research in this area.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, a pooled population-based analysis of five US states, which included California births from 1988–1997, did not find an association with maternal education [37]. A nationwide US study also suggested a lower risk of GCTs in higher-poverty areas, but poverty metrics were on the county-level, making results difficult to compare to our individual or census-tract level measures [38]. The small number of studies, and the varying measures of socioeconomic status used, suggest a need for more research in this area.…”
Section: Discussionmentioning
confidence: 93%
“…These inconsistent findings demonstrate the lack of basic professional and hospital infrastructure and the high mortality rate of childhood cancer. Furthermore, poverty is an important cofactor in this chain of unfavorable events …”
Section: Discussionmentioning
confidence: 99%
“…This fact, from the public health point of view, should direct attention to the triangle of poverty, malnutrition and early infections that most likely play a very important role in the etiology and incidence of childhood cancer in the PMI population. Recent studies [21] have suggested that the incidence of cancer among children living in poverty is much higher than in more affluent populations. This deficiency might be a factor that can account for the higher incidence of acute lymphoblastic leukemia in comparison to those children treated by the socialized healthcare systems in Mexico, in which the socioeconomic and cultural level is much higher.…”
Section: Discussionmentioning
confidence: 99%